Impact of COVID-19 confinement on the family climate of adolescents in the province of Concepción, Junín - Beraún Vásquez , Hilda Rosario (2022)
Objective. To determine the impact of COVID-19 confinement on the family climate of Huancayo adolescents. Methods. The research was basic, quantitative, correlational, non-experimental cross-sectional design. The sample consisted of 246 secondary school students from the Santa Rosa de Ocopa Educational Institution in the province of Concepción, Junín. The instruments used were the Moos family social climate scale and the validated and structured confinement questionnaire for its application. Results. There is a significant correlation rho =.531* betweenconfinement and family social climate. Eighty-five percent stated that their family had to make restrictions at the economic level because they were affected, 62% stated that they did not manage to understand classes virtually, 94% responded that they entertained themselves by playing online with their friends. At the level of relationship, development and stability was reported at an average level with respect to their family climate. Conclusions. The confinement had a significant impact on the family climate because they had to make economic restrictions due to the loss of their parents jobs. A large percentage stated that the virtual classes were not comprehensible. By not sharing activities in a face-to-face manner to which they are accustomed at this stage of their lives, adolescents express frustration, boredom and their escape was to play online games, creating addiction; which generated anxiety and problems in their emotional health.